Impacts of Melamchi Water Supply Project in Socio-Economic Development of Sindhupalchowak District of Nepal - Dahal, Dhundi Raj; Timsina, Tatwa P. (Journal of Advanced Academic Research, 2017)
The Melamchi Water Supply Project (MWSP) is considered to have been the most viable long-term alternative to ease the chronic water shortage situation within the Kathmandu Valley. The project has launched the separate project 'Social Upliftment Project' to improve the quality of life of community people. Besides that the project has divided its support field as buffer zone, health, education, income generation and rural electrification etc. to make the program more effective. So, the study aim is to explore the impact of Melamchi Water Supply Project in socio-economic status of local people of study areas. The study was conducted among the 8 VDCs of Sindhupalchowak district. Total, 404 respondents were selected randomly. The study found that MWSP had contributed in the field of agriculture, improving economic status of community people, education, infrastructure development and off-seasonal vegetable farming for income generating activities. There was a significant difference between the respondents of different VDCs regarding the contribution of MWSP. The Social Upliftment Program of MWSP should be continued and needed to extend in other hard-to-reach areas of district.